RANCANG BANGUN DISPLAY INFORMASI AKADEMIK DIGITAL DENGAN KONTROL MELALUI APLIKASI MOBILE ANDROID - Anafi, Muchlis Nanda Agung; Subur, Joko; Rifandi, Safriudin (J-Eltrik, 2023)
Information displays in the university environment play an important role in providing clear access to information and encouraging active participation from students, staff, and visitors. This study examines the importance of information displays at Hang Tuah University in encouraging academic community engagement, increasing awareness of campus activities, and expanding the scope of relevant information. The Faculty of Engineering and Marine Sciences at Hang Tuah University does not yet have an automatically updated academic information display. This information system uses IoT-based wireless communication controlled via Android. This methodology uses primary data collection and literature study. In the initial stage of hardware creation, the type and color of the Dot Matrix were selected. Meanwhile, in software creation, an Arduino Uno microcontroller and the MIT App Inventor application were used as system data control. The result of this final project is an information system that can be controlled via MIT App Inventor. This control is used to update the time, date, month, year and academic information data in the form of running text.